The Effect of Transformational Leadership Style and Teamwork Solidity on Employee Performance : JEL Classification: M12, M54, J24, H83, L32 - Vebriyanti Vebriyanti; A. Nur Insan; Syamsuddin Bidol (Newinera Publisher, 2026)
This study aims to determine the effect of transformational leadership style and teamwork solidarity on employee performance at the Makassar Harbormaster and Main Port Authority Office. This research was conducted at the Makassar Harbormaster and Main Port Authority Office. The design used in this study was a causality study. Data were collected through questionnaires, observations, and literature review. Data were analyzed using research instrument testing, classical assumption testing with multiple linear regression analysis, and hypothesis testing. The results of this study found and showed that the results of partial statistical tests (t-test) transformational leadership style has a positive and significant effect on employee performance, teamwork solidity has a positive and significant effect on employee performance. The results of simultaneous statistical tests (F-test) showed that transformational leadership style and teamwork solidity have a positive and significant effect on employee performance at the Makassar Harbormaster and Main Port Authority Office. Transformational leadership style and teamwork solidity have a very strong influence on employee performance of 84.7%. These results provide an illustration that the transformational leadership style and teamwork solidity that have been implemented at the Makassar Harbormaster and Main Port Authority Office have been very good and have made a major contribution to improving organizational performance.